Evaluation of Seal Effects on the Stability of Rotating Fluid Machinery - T. Iwatsubo; B. C. Sheng (International Journal of Rotating Machinery)
The stability of typical rotating fluid machinery such as single ahd multi-stage pumps is evaluated by using the finite element method. The individual contribution of the impellers, bearings and seals to the stability and the dynamic interactions of these fluid elements are examined. Various types of bearings and seals, such as annular smooth, parallel grooved and damper seals, are compared for better rotor stability. The effect of the operating conditions on the stability is also investigated. The results show that rotor stability can be easily improved by replacing the unstable fluid elements.